Event-based average consensus of disturbed MASs via fully distributed sliding mode control - Yao, Deyin; Li, Hongyi; Shi, Yang (IEEE transactions on automatic control, 2024)
Under undirected graph, we design the fully distributed static and dynamic event-triggered sliding mode controllers concerning the average consensus issues for single- and double-integrator multi-agent systems with perturbations. To guarantee the consensus convergence of disturbed first- and second-order multi-agent systems, two distributed sliding manifolds with respect to an odd function are firstly devised in this paper. Secondly, two types of event-triggered mechanisms, i.e., a static event-triggering mechanism and a dynamic event-triggering mechanism, are established to improve the utilization efficiency of network resources and avoid the continuous communication with neighbors. In both event-triggered sliding mode control strategies, the fully distributed event-triggered sliding mode control laws without global information of the multi-agent networks are proposed, and they can ensure the state trajectories of disturbed first- and second-order multi-agent systems to reach the average consensus. Meanwhile, the finite-time reachability of the specified sliding manifold can be guaranteed and Zeno behavior can be also averted. Thirdly, taking advantage of the Lyapunov stability theory and sliding mode control, sufficient conditions for the average consensus of single- and double-integrator continuous-time multi-agent systems are established. At the end, in order to show the validity of the proposed event-triggered sliding mode control strategies, a numerical simulation and comparative study are offered.